Effects of the virus satellite gene βC1 on host plant defense signaling and volatile emission - Salvaudon, Lucie (Landes Bioscience, 2013)
Tomato Yellow Leaf Curl China virus spreads together with its invasive vector, the silverleaf whitefly B biotype, which exhibits higher growth rates on infected plants. Previous studies indicate that the virus satellite gene βC1 accounts for the visible symptoms of infection and inhibits the constitutive expression of jasmonic acid (JA)—a phytohormone involved in plant defense against whiteflies—and of some JA-regulated genes. Here we present new details of the effects of on plant signaling and defense, obtained with (non-host) transgenic Arabidopsis thaliana and Nicotiana benthamiana plants. We found that JA induction in response to wounding was reduced in plants expressing βC1. This result implies that βC1 acts on conserved plant regulation mechanisms and might impair the entire JA defense pathway. Furthermore, transformed N. benthamiana plants exhibited elevated emissions of the volatile compound linalool, suggesting that βC1 also influences plant-derived olfactory cues available to vector and non-vector insects.